Antecedentes da participação das empresas no financiamento político: um estudo com dados gerados por meio de dinâmica de simulação empresarial (Business game) - Mrtvi, Valdete de Oliveira (2013)
Theoretical approaches prevalent in the field of business strategy (PORTER, 1980; BARNEY, 1991; PISANO and TEECE, 1997) generally do not explicitly consider political corporate behavior as a component in the broad set of elements that form the structure of strategy formulation and implementation. The little emphasis businesses are given in the political realm results in limitations to the understanding of the competitive environment and, consequently, reduces the explaining power of studies that set out to clarify the reasons for distinctive performances of companies. Salorio, Boddewyn and Dahan (2005) reinforce this perspective by noting that businesses are economical organizations, since their transactions balance costs, benefits, profits, market share, but need also to define and manage boundaries, as well as differentiate and integrate their members, stakeholders and operations. This involvement in a mix of bargain and no-bargain political-economic behaviors leads to defining businesses also as political organizations. Although this line of thinking still has a connotation of novelty for some, of a recycling of old ideas for others, or even seems to be guided by an attempt to retrieve matters that have always been dealt with laterally, Salorio, Boddewyn and Dahan (2005) emphasize that ‘the political is always there’. The main objective of the present project was to model simulated environment to test the antecedents of corporate political activity (HILLMAN, KEIM and SCHULER, 2004), and the specific objectives were: to model a simulator of the business and political environment, , and the specific objectives were: to model a simulator of the business and political environment of companies; to run the simulator and generate data about the antecedents of corporate political activity; to test the antecedents of corporate political activity as a strategic alternative in answer to businesses’ low performance, to the availability of resources and to the political activity of competitors; to test the interaction between market and nonmarket antecedents in order to explain political participation. The study may be characterized as descriptive with regard to its objectives, and as experimental in relation to its technical procedures. The study tested causal hypotheses, based on a quantitative methodology, where data was collected through 12 simulations, structured in a business game format, with nine companies in each simulation, in a total of 108 analysis units. The research subjects were Business Administration and Economy seniors at Londrina State University. Data analysis was conducted on STATA software to build regressions, using the statistical analysis model of panel regression, with fixed effects (WOOLDRIDGE, 2003), as the focus of the study was to analyze the companies’ information (decisions/performance) throughout time. Results indicate that: a) corporate inefficiency positively affects investment in electoral financing; b) investment in corporate political action happens to complement market actions, not in opposition to it; c) increased likelihood to invest in nonmarket is related to a lower performance than the competitors’; d) increased investment in nonmarket is not related to more active political action on the competitors’ part. No evidence was found that companies with more financial resources available are more politically active.